The Central and Eastern European countries and the European Union - Artis, Michael J.; Banerjee, Anindya; Marcellino, Massimiliano (Cambridge University Press, 2006)
Key aspects of the impact of the recent enlargement of the EU are analysed with reference to the Central and Eastern European countries. The book demonstrates that the enlargement could have profound consequences on both the new Member States and on the pre-accession members of the Union.